Monetary policy under the microscope: Intra-bank transmission of asset purchase programs of the ECB - Lisa Cycon; Michael Koetter (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Based on detailed loan portfolio data of a top-20 universal bank in Germany, we investigate the effect of unconventional monetary policy on corporate loan pricing. We can decompose corporate lending rates, thereby shedding light on intra-bank transmission of monetary policy. We identify policy effects on contracted customer rates, refinancing rates charged internally, markups earned by the bank, and loan volumes by exploiting the co-existence of eurozone-wide security purchase programs by the European Central Bank (ECB) and local fiscal policies that are determined autonomously at the district level where bank customers reside between August 2011 until December 2013. The purchase programs of the ECB reduced refinancing costs significantly. Local fiscal stimuli increased loan prices and margins earned. The differential effect of unconventional expansionary monetary policy given local tax environments is significantly negative. Lending volumes do not respond significantly though.
Keywords: E43; G18; G21; 330